PENGARUH PENGGUNAAN BOX POWER IGNITION TERHADAP KONSUMSI BAHAN BAKAR SEPEDA MOTOR KARBURATOR - Hengky Prasetyo Wibowo; Taufik Wisnu Saputra; Danar Susilo Wijayanto (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2023)
This study aims to determine the influence of voltage variations in box power ignition on the fuel consumption of a 2011 Honda Supra X 125 motorcycle. One way is to use box power ignition. The research method used is experimental. This research data was obtained using samples of Honda Supra X 125 motorcycle in 2011. The independent variable is the use of box power ignition with voltage variations of 14.4 V to 15.9 V. The dependent variable fuel consumption measured through stationary and road tests on predetermined routes. The maximum fuel consumption in stationary tests was obtained at a voltage variation of 14.7 V, measuring 2.54 ml/minute, a decrease of 0.98 ml/minute. The average fuel consumption increase was 3.55 ml/min. The maximum fuel consumption in road tests was obtained at a voltage variation of 15.3 V, measuring 28.13 m/ml, an increase of 11.46 m/ml. The average fuel consumptionincrease was 22.92 m/ml from the standard condition.